2020
DOI: 10.11591/ijai.v9.i1.pp65-72
|View full text |Cite
|
Sign up to set email alerts
|

Classification of multiclass imbalanced data using cost-sensitive decision tree C5.0

Abstract: The multiclass imbalanced data problems in data mining were an interesting to study currently. The problems had an influence on the classification process in machine learning processes. Some cases showed that minority class in the dataset had an important information value compared to the majority class. When minority class was misclassification, it would affect the accuracy value and classifier performance. In this research, cost sensitive decision tree C5.0 was used to solve multiclass imbalanced data proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Within this context, the six ML techniques used in this paper are It should be noted that although there exists an enhanced release of C4.5 algorithm, called C5.0 algorithm, the researchers sticked with the C4.5 because it is freely available unlike the enhanced version. Moreover, it is revealed that C4.5 can still produce somehow equal or better performance compared with C5.0 [37,38].…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…Within this context, the six ML techniques used in this paper are It should be noted that although there exists an enhanced release of C4.5 algorithm, called C5.0 algorithm, the researchers sticked with the C4.5 because it is freely available unlike the enhanced version. Moreover, it is revealed that C4.5 can still produce somehow equal or better performance compared with C5.0 [37,38].…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…The initial inference process of C4.5 utilizes the decision-making tree in common [ 57 ]. The quantified discrete function in C4.5 is used by using a decision tree to reply to the learnt function.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Febriantono et al [ 31 ] applied decision tree C5.0 of cost-sensitive type to work out imbalanced data issue of multiclass nature. At the first step, C5.0 algorithm was utilized by the decision tree model.…”
Section: Literature Reviewmentioning
confidence: 99%